Genetic basis of quantitative traits in chilli (Capsicum annuum L.) multi-parent populations based on skewness and kurtosis: Genetic basis of quantitative traits in chilli - Channabasava,; Siddu, Chindi Basavaraj; Ganesh, Prasad; Susmitha, Balaraju; Kalpana, Mugali Pundalik; Rao, Annabathula Mohan; Ramesh, Sampangi (Journal of Spices and Aromatic Crops, 2025)
The effectiveness of breeding and hence rate of genetic gain in chilli relies on understanding the genetics of target traits. Skewness and kurtosis, the third- and fourth-degree statistics, respectively, provide powerful tools to detect and characterize epistasis and the number of genes controlling traits. This study analyzed the genetics of three quantitative traits—average fruit weight (AFW), fruits plant⁻¹ (FP), and green fruit yield plant⁻¹ (GFY) - in 10 multi-parent (MP)-derived populations. Symmetrical platykurtic distributions in most MP populations indicated the predominance of numerous non-epistatic genes governing AFW, FP, and GFY, suggesting slow genetic gains with mild selection but rapid gains under intense selection. On contrary, positively skewed distributions in three MP populations indicated complementary epistatic genes with decreasing effects on FP and GFY. Additionally, leptokurtic distributions in two MPs indicated fewer genes controlling AFW and GFY, suggesting even mild selection is likely to be effective to improve these traits.